Anomalous Thermal Expansion in (Pr,Ca)MnO3 due to Orbital Ordering - Jussi Tikkanen; Simo Kauhala; Hannu Huhtinen; Petriina Paturi (Netherlands, 2022)
The monoclinic lattice parameters of the perovskite manganites Pr(1-x)CaxMnO3 were systematically measured by XRD at the Ca doping levels x=0.4, 0.5 and 0.1 at temperatures from 83 K to 403 K. The orbital ordering transition observed around 250 K at x=0.4 and x=0.5, located by SQUID magnetometry, was associated with a transient cell volume expansion of order 0.1%, during which the CO-related monoclinic distortion set in. The anomalous cell expansion, arguably driven by electrostructural disorder, was of sufficient magnitude to locally dominate the thermal expansion.